Literacy as Self-Improvement as Experienced by Louisa Clark in Jojo Moyes’s Me Before You (2013) - Ditha Seftyn Marshanda (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2023)
Literacy is one of the important things in life. It is the capability to use written, printed, or oral materials of social life to achieve goals and expand Knowledge or possibilities. This study focuses on Literacy as self-improvement depicted as experienced by Louisa Clark, and the reasons behind it. Data are in the form of citations taken from Jojo Moyes's Me Before You (2013). The steps to collect data are; to read repeatedly (Moyes, 2013), then collect data by citation the dialogues. Thus the study provides analysis and conclusions. This study uses New Literacy Studies by (T. Williams & A. Zenger, 2007) that point out that Literacy is important for personal transformation leading to self-improvement, which explains that the material conditions of life are improving Knowledge, language skills, and finances. In short, the result of this study established that Louisa Clark experienced Literacy as self-improvement in 3 aspects: Knowledge, language skills such as reading and speaking, and finances. Louisa also has several reasons leading to self-improvement, including; reasons for competing of employment opportunities and reasons for competing of career advancement supported by (Gee, 1992).